INFLUENCE OF Urochloa brizantha ON THE GROWTH AND NUTRITIONAL ABSORPTION OF TREE SPECIES - Santana, João Elves da Silva; Leles, Paulo Sergio dos Santos; Resende, Alexander Silva de; Dias, Monique Muniz Monteiro; Carvalho, Daniel Fonseca de; Lima, Thales Costa de (Floresta, 2020)
Influence of Urochloa brizantha on the growth and nutritional absorption of tree species. The objective of this study was to evaluate the influence of Urochloa brizantha var. Marandu on the growth and accumulation of macronutrients in the leaves of Cordia trichotoma and Guarea guidonia. Seedlings of tree species were transplanted to 18-liter pots and kept free of U. brizantha for three months. After that period, three treatments were adopted that consisted of the control (T0), two plants of U. brizantha per pot (T2) and four plants of U. brizantha per pot (T4). Growth and nutrient accumulation of tree species were evaluated after 84 days of coexistence with U. brizantha. The increment in diameter, of both tree species, leaf area and shoot dry matter of G. guidonia were significantly affected by the presence of U. brizantha, compared to the control. Significant differences were observed for the accumulation of potassium and magnesium in the leaves of C. trichotoma.